QT Dispersion and Age; Independent Predictors of Restenosis after Percutaneous Coronary Intervention - Aslanabadi, Naser; Moghadam, Sirous Vosooghi; Kazemi, Babak; Fadaei Fouladi, Daniel; Vaseghi, Golnaz; Eshraghi, Azadeh; Mahmoodian, Mehran; Tutunchi, Sarvnaz (Reviews on Recent Clinical Trials, 2017)
Introduction: There are no reliable non-invasive markers of restenosis after Percutaneous Coronary Interventions (PCIs). The aim of our study was to measure changes incorrected QT interval (QTc), corrected QT dispersion (QTcd), corrected T wave peak to end interval (TPEc) and corrected TPE dispersion (TPEcd) after PCI and to determine whether restenosis subsequently affects these indices. Methods: From 211 patients, who underwent successful PCI, 202 patients were referred for repeated coronary angiography in order to exclusion of coronary restenosis and included in this analysis. QTc, QTcd, TPEc and TPEcd indices were calculated just before PCI and 24 hours later. Results: Comparing pre procedural with post procedural results, median QTc and median QTcd decreased significantly after PCI procedure (from 447 to 440 ms, p=0.017 and from 46 to 40 ms,p=0.005; respectively). Corresponding changes of TPEc and TPEcD were not statistically significant. Multivariate analysis showed higher amounts of QTcd changes [Exp(B): 1.033, 95% CI: 1.018-1.051; P=0.025] and younger age[Exp(B): 1.074, 95% CI: 1.038-1.112; P=0.023] as independent predictors of restenosis. Area under the ROC curve indicated good predictive performance of QTcd changes (ΔQTcd) [AUC: 0.71, 95% CI: 0.51-0.86, P = 0.03] and age [AUC 0.68, 95% CI 0.62-0.74, p = 0.04] for restenosis after PCI. The best cut-off point for ΔQTcd was 6 msec, and for age was 52 years. The sensitivity and specificity of ΔQTcd≥6 ms to detect coronary restenosis were 73.2% and 71.4% respectively. The diagnostic accuracy of age was also similar, the sensitivity and specificity of age≤ 52 years were 68.1% and 74.3% respectively. Conclusion: The Higher differences between pre and post PCI QTcd may be an inexpensive and simple predictor of restenosis after a previously successful coronary angioplasty. It seems that these findings encourage us to re-think about using QTcd as a simple ECG predictor for sustained coronary patency after angioplasty.
Keywords: restenosis